THE ROLE OF MORAL DEVELOPMENT OF CHILDREN OF PRESCHOOL AGE IN PREPARING THEM FOR SCHOOL - Hasanova, P.M (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The world in which we live is characterized by global changes, which leads to the need to solve many social problems in society. These include the issue of spiritual and moral preparation of children for school. The article reveals the essence of the socio-moral and cultural development of preschoolers, the tasks facing the teaching staff of the kindergarten in this regard. The statement of the cultural and moral education of children in kindergarten is considered; the ways of forming values that influence this education are indicated. The author believes that the most important in the moral and cultural development of children is the independent acquisition of knowledge and cultural values. In addition, it is important to live and work among people, to justify their position, without turning the discussion into a conflict. For this, children develop skills of joint work on assigned tasks, the ability to use their individual qualities in teamwork. A variety of cultural events, accustoming to work, involving parents in the work, and continuing the formation of the necessary skills in the family will contribute to the formation of the necessary spiritual level of development in children. Thus, the spiritual world of children will become more diverse, schooling and education will be more successful.